PERANCANGAN SISTEM PENCATATAN DAN PELAPORAN DIVISI KARTU DI KOPERASI INDOSAT MENGGUNAKAN TEKNIK PARALLEL PROCESSING COMPUTING - Erman Arif (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
World development Cellular telecommunications is now growing rapidly, and if it is tailored to the needs of the community, this will greatly affect the quality of telecommunications. The Kopindosat Card Division, which is one of the official dealers of PT. Indosat. The purpose of this is to produce accurate and relevant data. And the technique used is parallel processing computing, which is processing that uses more than one CPU. In this paper the author only limits the range of inputting POs, allocation mutations, and making reports (daily, weekly, and monthly). All of these processes are carried out with the Modern Computing Technique, Grid Computing which utilizes processing power and Process strength to calculate one job. The system aims to collect, send and process data quickly, precisely and produce information that is both timely and effective. This is important for leaders in making decisions and policies, in order to help and facilitate administrators, in the implementation of the sales system. The proposed system procedure does not differ much from the current system on SEV. In this proposed system there are a number of proposed changes, namely the SEV sales transaction process on the TLD. Where in the current system, the SEV sales process still uses mobile phones to do top-ups, which is done by the administrator Keyword: Parallel Processing, Grid Computing, Indosat Cooperative